2021
DOI: 10.3390/polym13060867
|View full text |Cite
|
Sign up to set email alerts
|

Creep Response of Carbon-Fiber-Reinforced Composite Using Homogenization Method

Abstract: The homogenization theory, used for the study of differential equations with periodic coefficients, with a rapid variation, is used in the paper for the analysis of the creep phenomenon of composite materials, reinforced with fibers. Generally, a polymer composite having a matrix with a viscoelastic response manifests a creep behavior. A good knowledge of mechanical constants allows us to predict the time response under the action of a load, which is important in engineering. The homogenization method is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In this way, the finite element method proves to be a powerful tool for calculating the mechanical properties of a multiphase material. Compared to the already known and applied methods, such as the use of micromechanical models, homogenization theory and Mori-Tanaka formalism, the finite element method is added, as a useful and relatively simple method of determining the coefficients of the constitutive equations of the material [54]. A future way of developing the topic is to improve the procedure by adding new results on how the finite element method can be used together with a parametric approach to the problem.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this way, the finite element method proves to be a powerful tool for calculating the mechanical properties of a multiphase material. Compared to the already known and applied methods, such as the use of micromechanical models, homogenization theory and Mori-Tanaka formalism, the finite element method is added, as a useful and relatively simple method of determining the coefficients of the constitutive equations of the material [54]. A future way of developing the topic is to improve the procedure by adding new results on how the finite element method can be used together with a parametric approach to the problem.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The constitutive equation (in uniaxial stress and isothermal conditions) is written as such [1]: To evaluate D 66 , which is used to measure time-dependent shear modulus G 12 , [±45] 2s laminates are tested under tensile creep loading condition similar to that of 90-degree specimens. Using the transformation presented in [28] for θ = 45 o (the angle between global and local coordinates (see Figure 1)), it can be shown that:…”
Section: (I) Homogeneitymentioning
confidence: 99%
“…To evaluate , which is used to measure time-dependent shear modulus laminates are tested under tensile creep loading condition similar to that of 90-degree specimens. Using the transformation presented in [ 28 ] for (the angle between global and local coordinates (see Figure 1 )), it can be shown that: where x and y are the longitudinal and transverse directions. Moreover, the shear stress is found to be , with being the constant applied stress in the creep test.…”
Section: Viscoelastic Modelsmentioning
confidence: 99%
“…Such synergy, as we have already established earlier, can be complex reinforcement, namely, fiber plus reinforcing bars, improved concrete characteristics due to their nanomodification or the same fiber reinforcement with fibers [ 30 , 31 , 32 , 33 , 34 ]. However, in addition to the above methods, it is also promising to create so-called differentiated building elements, particularly in their cross section [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mineral impregnated carbon fiber composites are a new type of reinforcement for construction. Compared to steel reinforcement, carbon fiber reinforcement has a much higher tensile strength and a significantly lower weight [ 22 , 24 , 31 , 33 , 35 , 38 , 39 , 41 , 42 , 43 , 44 , 47 , 49 , 51 , 55 , 59 ]. At present, the technology of reinforcing concrete bending elements with carbon fiber sheets is popular [ 44 , 59 ].…”
Section: Introductionmentioning
confidence: 99%